2007
DOI: 10.1007/s00701-007-1241-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactate therapy upon cognitive deficits after traumatic brain injury in the rat

Abstract: This study indicates that the intravenous infusion of 100 mM L-lactate provided the optimal concentration of the substrate to ameliorate cognitive impairment, probably via the regeneration of ATP following TBI in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 50 publications
4
61
2
1
Order By: Relevance
“…Rats with traumatic brain injury had improved performance on a maze test after intravenous lactate therapy. This correlated with improved maintenance of ATP levels in the injured area of the brain occurring after lactate, but not after saline treatment [17,18]. Also, in a small clinical study, patients with traumatic brain injury who had higher lactate uptake by the brain relative to arterial lactate had improved neurologic function 6 mo later [19].…”
Section: Fig 4 Scattergram Of Admission Lactate Values Of Survivorsmentioning
confidence: 85%
See 1 more Smart Citation
“…Rats with traumatic brain injury had improved performance on a maze test after intravenous lactate therapy. This correlated with improved maintenance of ATP levels in the injured area of the brain occurring after lactate, but not after saline treatment [17,18]. Also, in a small clinical study, patients with traumatic brain injury who had higher lactate uptake by the brain relative to arterial lactate had improved neurologic function 6 mo later [19].…”
Section: Fig 4 Scattergram Of Admission Lactate Values Of Survivorsmentioning
confidence: 85%
“…It is unknown what level of exogenous lactate neurons would need to have available for optimal function. Interestingly, in head injury animal studies where lactate was administered, there was a survival advantage with concentrations of 5-100 mmol/L [10,17,18].…”
Section: Fig 4 Scattergram Of Admission Lactate Values Of Survivorsmentioning
confidence: 97%
“…The normal human brain already shows striking differences in lactate/pyruvate ratio from plasma, which suggest that lactate is a physiologic fuel for neurons (12). Accordingly, it has been speculated that lactate might be a useful therapy following TBI (13,14). However, a conundrum arises as a result of the common observation that excessive lactate accumulation following TBI correlates with poor prognosis (15)(16)(17).…”
mentioning
confidence: 88%
“…This limitation applies not only to the current study demonstrating an SP treatmentinduced reduction in cortical neuronal injury after experimental TBI but to the most, if not all, of the prior studies of SP treatment efficacy after other acquired neurological injuries in which circulating fuel concentrations have not been assessed. Since serum pyruvate levels will also increase after lactate infusion (LaManna et al, 1993), this limitation applies as well to those studies reporting neurological benefits in TBI models after lactate administration where pyruvate, and frequently glucose, levels have not been assessed (Chen et al, 2000a;Rice et al, 2002;Levasseur et al, 2006;Holloway et al, 2007). Future work on supplemental monocarboxylate administration after brain injury will no doubt benefit by including measures of the administered substrate on serum and extracellular levels and=or the metabolic rates of pyruvate, lactate, and glucose as well as by directly comparing effects of separate administration of each of these substrates in the injury model of interest.…”
Section: Monocarboxylate Use and Effects After Brain Injurymentioning
confidence: 99%
“…For example, it is reported that intravenous lactate accumulates in extracellular fluid and attenuates TBI-induced reductions in extracellular glucose (Chen et al, 2000a(Chen et al, , 2000b, reduces TBIinduced cognitive deficits (Rice et al, 2002), attenuates reductions in cortical adenosine triphosphate (ATP) levels (Holloway et al, 2007), and improves oxygen consumption after TBI (Levasseur et al, 2006). Exogenous lactate administered via cerebral microdialysis was also reported to reduce glutamate-induced neuronal damage (Ros et al, 2001), and inhibition of monocarboxylate transporters (MCT) to block lactate uptake was reported to increase neuronal damage after cerebral ischemia (Schurr et al, 2001).…”
mentioning
confidence: 99%